The contribution of foliar micromorphology and anatomy to the circumscription of species within the Chusquea ramosissima informal group (Poaceae, Bambusoideae, Bambuseae) - Leandro, Thales D. [UNESP]; Scatena, Vera L. [UNESP]; Clark, Lynn G. (Springer, 2017)
Chusquea is a diverse but monophyletic genus of Neotropical woody bamboos from primarily montane forests that comprises four well-supported lineages: subg. Magnifoliae, subg. Platonia, subg. Rettbergia, and the Euchusquea clade (comprising subg. Swallenochloa and subg. Chusquea). However, the relationships among clades or taxa within the Euchusquea clade inferred from molecular data are mostly not congruent with those inferred from morphological evidence, consequently limiting our ability to understand species relationships. In this study we generated foliar micromorphological and anatomical data for the Chusquea ramosissima informal group (Chusquea ramosissima, C. tenella, and C. tenuiglumis), and for the putative new species from Bolivia in this group, in order to test the value of these types of data for defining species and to seek potential synapomorphies for this group. Our results demonstrate that epidermal features, mainly with regard to the stomatal apparatus, proved to be more valuable in distinguishing species than anatomical characters. The presence of horizontally elongated silica cells over the veins and adaxial arm cells with invaginations from the abaxial side was shared by all the studied species but is not unique to this group. The type of trichomes, shape of silica bodies, type of arm cells, and midrib structure may be useful to lesser degree. All four species exhibited intraspecific variation in development of the papillae on the long cells. Support for the recognition of the new species from Bolivia is provided by micromorphological characters. An identification key based on leaf blade features is provided for the four studied species.
Keywords: Chusqueinae; Leaf; Monocotyledons; Poales; Woody bamboos